Re-visiting the past in search for silver-lining: Moroccan students' perceptions of technology-mediated faculty practices under COVID-19. - Zyad, Hicham (Journal of North African Studies, 2024)
Despite the wide-ranging research on technology-mediated learning, which has contributed immensely to a better understanding of how best it can be implemented, lockdowns during COVID-19 times have revived debates on teacher preparedness to adequately engage in this modality of instruction. Research-validated evidence has shown that a complex combination of technology, pedagogy and content is necessary for impactful teaching practices. Thus, the present paper reports on a qualitative study that investigated students' perceptions of their teachers' performance during the lockdown period. Online interviews and focus groups were conducted with a cohort of 30 university students. The students were selected by means of purposeful sampling informed by a set of pre-defined criteria. Overall, the students reported that most of their teachers utilised asynchronous teaching modalities. Also of interest was the finding that a small proportion of faculty varied the instructional deliverable with a clear intent to cater for a wider spectrum of student learning pace and style. Under COVID-19, additionally, distance education was hugely crippled by student psychological ill-being. One of the implications of these findings, among others, is the pressing need, now more than ever, for comprehensive and intensive teacher professional programs focused on technology-enhanced methodology.